Humor as a Defense Mechanism during the Holocaust - Osṭrover, Ḥayah (Interpretation, 2015)
This article documents narratives of fifty-five Jewish Holocaust survivors who were teenagers during the Holocaust period and highlights their ability to cope with Holocaust atrocities by using various types of humor as a defense mechanism.